Assessment of the Understanding of Concussion and Care Protocols Amongst Student Athletes and Coaches: A Qualitative Study - Subramaniam, Aditya; Tan, Ronald Ming Ren; Chan, Derrick; Ng, Zhi Min; Dong, Chao Yan; Feng, Jasmine Xun Yi; Chong, Shu-Ling (Frontiers in Pediatrics, 2020)
Background: Pediatric sports-induced concussions have become a topic of interest and concern in the scientific community. Already, the literature is rich with studies that have identified numerous short-term and long-term consequences of childhood sports-induced concussions. However, there are very few studies that have identified how well the students who participate in concussion-prone sports and their coaches understand these consequences and how they can be avoided. This study aimed to explore student athletes’ and their coaches’ understanding of the concept of concussion and how it is managed both immediately after the injury occurs and during long-term recovery. Methods: This study utilized a qualitative design. The study was conducted in local and international schools in Singapore. Participants were recruited through purposive sampling. 42 student athletes aged 13-18 who participated in rugby, softball, football, cricket, volleyball, and/or water polo were recruited. 14 coaches who coached these same sports were also recruited. Four focus groups and three semi-structured interviews were conducted. Data collected were then analyzed with thematic analysis. Risk factors were assessed through four domains of focus: understanding of what concussion is; attitudes towards concussion; existing protocols for treating concussion; and return-to-school and return-to-play protocols. As this is a qualitative study, outcome measures were not identified. Results: Analysis of the data revealed four themes for each group. For student-athletes these included: limited understanding of concussion; non-reporting of injuries; variable supervision of athletes; and a lack of established return-to-school and return-to-play guidelines. For coaches these included: variable understanding of concussion; insufficient formal training in concussion management; limited medical support in managing injuries; and lack of understanding and adherence to return-to-school and return-to-play protocols.  Conclusions: Of the themes identified, the most pressing was a lack of clearly defined return-to-play guidelines. This is an urgent issue that needs to be jointly addressed by healthcare professionals and schools with evidence-based guidelines.